HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENCEGAHAN COVID-19 PADA MAHASISWA FIKES UIA TAHUN 2021 - Dela Aviantika; Siti Rapingah (Afiat, 2021)
Covid 19 is an infectious disease that is currently being faced by the world, because in addition to causing death, it also spreads very quickly. Knowledge about Covid-19 is important in Covid-19 prevention behavior. This study aims to identify the relationship between knowledge and Covid-19 prevention behavior in the student environment of FIKes UIA. The research method used descriptive correlative by using a cross sectional design. The population of 369 people with a total sample of 79 people with the sampling technique is purposive sampling. The research instrument used a questionnaire. Bivariate data analysis with chi-square test =5%. The results method that 59 respondents (74.7%) had a good level of knowledge, of which 38 respondents (48.1%) had positive behavior and 21 respondents (26.6%) had negative behavior. And for students who have a sufficient level of knowledge as many as 20 respondents (25.3%), of that number 10 respondents (12.7%) have positive behavior and 10 respondents (12.7%) have negative behavior. The results of the analysis using Chi-Square obtained a p value of 0.001. The conclusion is that there is a relationship between the level of knowledge about Covid-19 and Covid-19 prevention behavior in the FIKes UIA Student environment in 2021. Suggestions for students to provide examples of behavior that comply with health protocols and always update knowledge related to Covid-19, because health students are one of the role models for society.